The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s00198-011-1620-3
|View full text |Cite
|
Sign up to set email alerts
|

Treatment satisfaction and persistence among postmenopausal women on osteoporosis medications: 12-month results from POSSIBLE US™

Abstract: Lower treatment satisfaction was associated with a 22% (1/0.82) to 67% (1/0.60) increased risk of discontinuation/switching osteoporosis medication during 1 year of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 34 publications
1
32
0
1
Order By: Relevance
“…Recent studies have shown that treatment satisfaction is higher for patients receiving subcutaneous twiceyearly denosumab than for once-weekly alendronate as assessed by the Preference Satisfaction Questionnaire (13,14). The results from our study build upon those from another recent study using the TSQM questionnaire that demonstrated that postmenopausal women with osteoporosis who reported lower satisfaction (global satisfaction domain) with their osteoporosis treatment were 37% more likely to discontinue/switch medications than women who reported higher satisfaction (5). Additionally, since poor adherence with bisphosphonate therapy increases fracture risk in women with postmenopausal osteoporosis (15)(16)(17), our results underscore the importance of treatment satisfaction as it relates to adherence and optimal osteoporosis treatment.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Recent studies have shown that treatment satisfaction is higher for patients receiving subcutaneous twiceyearly denosumab than for once-weekly alendronate as assessed by the Preference Satisfaction Questionnaire (13,14). The results from our study build upon those from another recent study using the TSQM questionnaire that demonstrated that postmenopausal women with osteoporosis who reported lower satisfaction (global satisfaction domain) with their osteoporosis treatment were 37% more likely to discontinue/switch medications than women who reported higher satisfaction (5). Additionally, since poor adherence with bisphosphonate therapy increases fracture risk in women with postmenopausal osteoporosis (15)(16)(17), our results underscore the importance of treatment satisfaction as it relates to adherence and optimal osteoporosis treatment.…”
Section: Discussionsupporting
confidence: 68%
“…In postmenopausal osteoporosis, important treatment goals include effectiveness, optimal adherence, tolerability, and patient satisfaction. High treatment satisfaction is associated with greater persistence with treatment in postmenopausal osteoporosis (5). Women who reported lower global satisfaction with their oral osteoporosis medication were 37% more likely to switch or discontinue their medication as compared with women who reported higher global satisfaction (5).…”
mentioning
confidence: 99%
“…There is currently no indication for increased mammographic or cervical smear screening in MHT users. Women taking non-estrogen based treatments for osteoporosis should be reviewed to ascertain continued use of therapy and monitoring response with bone mineral density assessments or biochemical markers to maximise benefits and minimise risks [49,50].…”
Section: Follow-up and Assessmentmentioning
confidence: 99%
“…Reasons for nonadherence are multifactorial and include convenience and frequency of the dosing regimen, perceived efficacy, and side effects [7,8]. Results from a large, longitudinal study of postmenopausal women who were prescribed treatments for osteoporosis found that women who were less satisfied with their osteoporosis treatment were more likely to discontinue treatment within the first year than women who were more satisfied with their osteoporosis treatment [9].…”
Section: Introductionmentioning
confidence: 99%